2014
DOI: 10.18848/2325-1077/cgp/v09i02/55082
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Electrification with Renewable Energies on Local Economies

Abstract: For India it is crucial to promote rural electrification to raise the well-being of the people in its rural areas, which have a larger number of population and households than its urban areas. In rural areas of India, two types of electrification are in progress. One is the electrification through connecting to conventional grid. The other is the electrification with renewable energies such as solar, biomass, hydro and so on. Many studies prove positive socio-economic impacts of the electrification with renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Apart from the preceding sections, there are some other notable qualitative observations from the villages that are highlighted in this section. It is noted that electrification in the four villages did not translate directly into a substantial increase in income or working time, as suggested in some literature [23,[69][70][71]. This is mainly because of two reasons: Firstly, the villagers, who were mostly farmers and fishermen, could not directly increase their working time or productivity through the use of electricity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Apart from the preceding sections, there are some other notable qualitative observations from the villages that are highlighted in this section. It is noted that electrification in the four villages did not translate directly into a substantial increase in income or working time, as suggested in some literature [23,[69][70][71]. This is mainly because of two reasons: Firstly, the villagers, who were mostly farmers and fishermen, could not directly increase their working time or productivity through the use of electricity.…”
Section: Discussionmentioning
confidence: 91%
“…Electrification is generally thought to bring about increases in household income due to extended productive activities [23,[69][70][71]. In some cases, however, there has been evidence that only when productive activities take place within the household, electricity impacts the most [72].…”
Section: Expenses On Electricitymentioning
confidence: 99%
“…The profitability of these business activities grows by 100-150% [13,14]. Manufacturing companies in developed countries report that the substation of electrical power for heat and other energy carriers in various production processes yields the following results in the long run:…”
Section: Economic Effects Of Electrificationmentioning
confidence: 99%
“…This has in fact had an impact on opening jobs, new income, and household expenses [13]. Conceptually it was also found that the use of RE had an impact on the socio-economic conditions of beneficiary communities such as increased income, business productivity, new jobs, and community capacity [14][15][16]. However, after three years of operation, solar mini-grid management found various problems such as power theft, payment delays, damaged components and even reduced electrical power performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have looked at the feasibility, potentials analysis, and technical aspects of Centralized PV mini-grid [3,17], impact of solar PV mini-grid [15,[18][19][20], and renewable energy policy [21][22][23][24]. How to manage community-based centralized PLTS and what factors influence it is still rarely explored, especially in remote villages in Indonesia.…”
Section: Introductionmentioning
confidence: 99%